Diversification Among Cryptoassets: Bitcoin Maximalism, Active Portfolio Management, and Survival Bias - Weizhi Sun; Ladislav Kristoufek (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Cryptoassets, particularly Bitcoin, have attracted the attention of institutional investors during the latest price rallies of 2020 and 2021. The need for cryptoassets apart from Bitcoin in their portfolios is mostly unexplored in the current literature, and the general perception of diversification benefits within cryptomarkets mostly builds on popular beliefs. The current study is a deep dive into active and passive investment strategies focusing on specifics of cryptoassets, the most important of which is the survival bias in the portfolio dataset construction and its implications. We show that survival bias does in fact drive the results at their very core and that the differences between using the backward-looking subset of assets and actual assets available at the time of portfolio construction are substantial and lead to completely different implications and investment suggestions. It turns out that active portfolio management does not pay off in most instances compared to simply holding Bitcoin.
Keywords: G11; G15; G19; G23; 330; cryptocurrencies; cryptoassets; Bitcoin; diversification; portfolio management; survival bias